The Role of Topical Glucocorticosteroid Methylprednisolone Aceponate in External Therapy of Atopic Dermatitis in Children - Yuliya G. Levina; Anna A. Alekseeva; Elena A. Vishneva; Kamilla E. Efendieva; Elena A. Dobrynina (Педиатрическая фармакология)
The article describes the main characteristics of local glucocorticosteroids (GCS) which are the «gold standard» for external therapy of atopic dermatitis allowing to achieve control over  the disease quickly and effectively. Methylprednisolone aceponate 0.1%  — non-fluorinated local GCS, the drug with the most favourable  therapeutic index, the efficacy and safety of which has been  demonstrated in numerous randomized trials — is the optimal  therapeutic option in the treatment of AtD in children from 4 months.